Consumer acceptance and usage of digital signature technologies - Lääveri, Lassi (2021)
Digital signatures have grown in popularity as a method of signing and collecting signatures on documents. After the movement and contact restrictions posed by the coronavirus pandemic in 2020, the popularity of the technology exploded. Technically speaking, digital signatures are created using asymmetric cryptography. Asymmetric cryptography enables the verification of authentication, integrity of the document and signatory nonrepudiation. Digital signatures hold a similar legal status to that of a traditional signature within the European union. Most of the studies focusing on digital signatures have been focusing on the technical aspects of the phenomenon, while the users’ perspective is often neglected. This study is bases on the presumptions provided by technology acceptance studies, in the field of information technology to study the factors affecting user acceptance of digital signature technologies. The unified theory of acceptance and use of technology (UTAUT) is a model that is used to study use behaviour of technologies and information systems. In the model performance expectancy and effort expectancy are two of the constructs that affect behavioural intention. Therefore, it is valuable to study what performance and effort actually mean in the context of digital signatures from the users’ point of view. While this study bases on the technology acceptance studies and especially the UTAUT model, it is important to note that the study does not attempt to be an extension to UTAUT or use UTAUT to predict behaviour. This study identified six different main categories of parameters that the users judge the performance of digital signatures: efficiency, information security, convenience, comparative performance, scalability functions and other factors. The effort and ease is judged basing on service-specific user experience, information availability, comparative ease and contextual factors. The implications of the study for theory and practice as well as limitations and future research suggestions are provided in the discussion chapter.